Freedom and responsibility in Jean-Paul Sartre’s existentialism: A philosophical review - Milton Thorman Pardosi (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
Amid growing ethical uncertainty in the digital and globalized era, questions about individual freedom and responsibility have become increasingly relevant. This study explores the concepts of existence and essence in the philosophy of Jean-Paul Sartre, with a focus on the implications of freedom and responsibility in modern human life. Highlighting the relevance of Sartre’s existentialism in today’s social context, the research aims to contribute to a deeper understanding of individual moral and ethical responsibility. Using a literature review and thematic analysis of key works such as Being and Nothingness and Existentialism is a Humanism, the study examines Sartre’s ideas on existence preceding essence, the burden and necessity of freedom, and the ethical challenges it presents. The analysis reveals that Sartre positions freedom as central to human existence, enabling self-determination while demanding responsibility for one’s choices. In contemporary society, especially amid digitalization and globalization, these ideas remain vital in addressing issues of alienation, authenticity, and ethical decision-making. The study concludes that Sartre’s philosophy offers significant insights for moral education and personal development, encouraging individuals to live more consciously, authentically, and responsibly in an increasingly complex world.   Di tengah ketidakpastian etika yang semakin meningkat pada era digital dan globalisasi, pertanyaan tentang kebebasan dan tanggung jawab individu menjadi semakin relevan. Penelitian ini mengkaji konsep eksistensi dan esensi dalam filsafat Jean-Paul Sartre, dengan fokus pada implikasi kebebasan dan tanggung jawab dalam kehidupan manusia modern. Penelitian ini menyoroti relevansi eksistensialisme Sartre dalam konteks sosial masa kini, serta bertujuan memberikan pemahaman yang lebih mendalam tentang tanggung jawab moral dan etika individu. Melalui kajian pustaka dan analisis tematik terhadap karya-karya utama seperti Being and Nothingness dan Existentialism is a Humanism, studi ini membahas pemikiran Sartre mengenai eksistensi yang mendahului esensi, kebebasan sebagai beban sekaligus keharusan, serta tantangan etis yang ditimbulkannya. Hasil analisis menunjukkan bahwa Sartre menempatkan kebebasan sebagai inti dari eksistensi manusia, yang memberi kemampuan untuk menentukan diri, namun juga menuntut tanggung jawab atas setiap pilihan. Dalam masyarakat kontemporer, terutama di tengah digitalisasi dan globalisasi, gagasan-gagasan ini tetap relevan dalam menghadapi isu keterasingan, keaslian diri, dan pengambilan keputusan etis. Penelitian ini menyimpulkan bahwa filsafat Sartre memberikan wawasan penting bagi pendidikan moral serta pengembangan pribadi, mendorong individu untuk hidup secara lebih sadar, autentik, dan bertanggung jawab di tengah kompleksitas dunia modern.